Keunikan Metadologi Hafazan al-Quran Deobandy dari India - Ariffin, Sedek; Mohamad, Sabri; Saad, Shaharuddin; Zakaria, Mohd Zaini; Nik Abdullah, Nik Md. Saiful Azizi; Md Said, Mohd Sa’di; Azmi, Riswadi (Penerbitan Universiti Malaya, 2011)
There are several methods to memorize the Qur’an in Malaysia. These methods have been studied and adopted by the huffaz. The methods of memorizing the Qur’an is an important matter to ensure that students can memorize and remember the Qur’an as soon as possible after they become Hafiz al-Qur'an. Method of memorization is the basic technique in memorizing the Qur’an. However different techniques and approaches in each method will give a different impact on the quality of memorization. There are many methods of memorization in Malaysia are imported from foreign countries and among them is the Deobandy method from India. Deobandy method has some unique and special privilege compare to other method. Deobandy method adopted a few techniques such as memorizing preparation, sabak, para sabak, ammokhtar, halaqah dauri and so on.